Five little monkeys wash the car - Christelow, Eileen (New York : Scholastic Inc., 2001)
Five little monkeys wash the family car before trying to sell it, but that is only the beginning of their adventures with the old heap.
"Published ... by arrangement with Clarion Books, a Houghton Mifflin Company imprint."--Title page verso.
106831
Keywords: Automobiles -- Juvenile fiction; Monkeys; Crocodiles; Stories in rhyme; Stories in rhyme